2016
DOI: 10.1177/0284185115588124
|View full text |Cite
|
Sign up to set email alerts
|

Bosniak classification system: a prospective comparison of CT, contrast-enhanced US, and MR for categorizing complex renal cystic masses

Abstract: Background The Bosniak classification was originally based on computed tomographic (CT) findings. Magnetic resonance (MR) and contrast-enhanced ultrasonography (CEUS) imaging may demonstrate findings that are not depicted at CT, and there may not always be a clear correlation between the findings at MR and CEUS imaging and those at CT. Purpose To compare diagnostic accuracy of MR, CEUS, and CT when categorizing complex renal cystic masses according to the Bosniak classification. Material and Methods From Febru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
49
2
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(53 citation statements)
references
References 20 publications
0
49
2
2
Order By: Relevance
“…Indeed they found that CEUS and MRI results were both in agreement with CT diagnosis with a high kappa score (0.86 and 0.91, respectively), and they concluded that enhanced CT should remain the gold standard for the Bosniak classification. 19 However, these discrepancies with the present results could be explained by different methods. First, in their study, they included a majority of Bosniak 2 (n = 27), which are less problematic for CT diagnosis than Bosniak 2F or 3 cysts, representing just 19 cases, whereas we included only such cysts.…”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…Indeed they found that CEUS and MRI results were both in agreement with CT diagnosis with a high kappa score (0.86 and 0.91, respectively), and they concluded that enhanced CT should remain the gold standard for the Bosniak classification. 19 However, these discrepancies with the present results could be explained by different methods. First, in their study, they included a majority of Bosniak 2 (n = 27), which are less problematic for CT diagnosis than Bosniak 2F or 3 cysts, representing just 19 cases, whereas we included only such cysts.…”
Section: Discussioncontrasting
confidence: 96%
“…reported different results in a prospective study including 46 patients. Indeed they found that CEUS and MRI results were both in agreement with CT diagnosis with a high kappa score (0.86 and 0.91, respectively), and they concluded that enhanced CT should remain the gold standard for the Bosniak classification . However, these discrepancies with the present results could be explained by different methods.…”
Section: Discussioncontrasting
confidence: 41%
“…Recent studies 4,[6][7][8][9][10][11][12][13][14][15][16] have demonstrated that the sensitivity and specificity of contrast-enhanced sonography in characterizing a lesion as benign or malignant are higher than those of contrast enhanced CT and contrast enhanced MRI. With the increased accuracy of renal mass characterization on contrast-enhanced sonography, there is a need to modify the Bosniak classification system to more appropriately provide a probability of malignancy and the resultant change in follow-up and treatment.…”
mentioning
confidence: 99%
“…However, multiple smaller single-site studies had similar findings. [5][6][7][8][9][10][11][12][13][14][15] With the recent US Food and Drug Administration approval of an ultrasound contrast agent for liver applications, it is expected that off-label use of contrastenhanced sonography to characterize renal masses will increase substantially in the United States. It would be beneficial to develop a modification of the Bosniak classification, including contrast-enhanced sonography, to aid in future studies for prospectively determining whether contrast-enhanced sonography can appropriately change clinical management, especially in Bosniak 3 lesions.…”
mentioning
confidence: 99%
“…Complex cysts analyzed in this article did not have calcifications, were not localized in the medial aspect of the kidney and no extremely obese patients were examined. As with gray scale ultrasound examination, CEUS is more sensitive to differentiate surgical from non‐surgical kidney cysts that are small in size compared with CT examination (partial volume effect) and MRI examination (lower spatial resolution) …”
mentioning
confidence: 99%